Interoperability and Quality Control Effectiveness in Primary Healthcare Centers: Evidence from Public Health Centers - Mely Pakaya; Asna Aneta; Zuchri Abdussamad; Yanti Aneta (Jurnal Ilmiah Manajemen Kesatuan, 2026)
This study examines how information system interoperability within public primary healthcare networks influences the effectiveness of quality control processes. Using a cross-sectional mixed-methods design, data were collected from heads of public health centers, quality officers, and district-level health data managers. Quantitative measures included the interoperability maturity index and index, complemented by qualitative interviews and document analysis to examine feedback mechanisms and governance practices. Multivariate regression analysis showed that interoperability maturity was positively associated with quality control effectiveness. Mediation analysis revealed that feedback loop intensity significantly mediated this relationship, while moderation analysis indicated that leadership and data governance strengthened the impact of interoperability on quality control effectiveness. These findings highlight that interoperability improves quality control not only through technical integration but also through structured feedback processes and strong governance arrangements. The study contributes a measurable and auditable process model for data-driven quality improvement in primary healthcare and underscores the importance of semantic standardization, disciplined feedback cycles, and institutionalized data governance to support sustainable quality improvement.